Role of additive and multiplicative age correction factors in sire evaluation of Hariana cattleD S DALAL - DALAL, D S; KHANNA, A S (The Indian Journal of Animal Sciences, 2010)
Data on 491 first lactation records of Hariana cows sired by 41 sires maintained from 1995-2006 at 5 farms, viz. Germ Plasm Unit, CCSHAU, Hisar; Government Livestock Farm, Hisar; Kurukshetra Gaushala, Hisar; Gaushala Bhiwani and Gaushala Jind under ICAR project entitled, “Genetic Improvement of Indigenous Breeds of Cattle (Hariana Unit)” were analyzed for developing and evaluating the efficiency of additive and multiplicative age correction factors. Age at first calving was classified into 11 classes with an interval of 120 days between classes. The model used for least squares analysis and for deriving the age correction factors included herd, period of calving, season of calving and age groups as fixed effects and lactation length as a covariate. Both the age correction factors were equally effective on the basis of mean, F-ratio and R2 value, while multiplicative age correction factors were more effective in retaining similar coefficient of variation (CV) for all subclasses of age groups as that of uncorrected data and reducing the residual variance as compared to uncorrected and additively corrected data. Out of 41 sires; 19 sires were having positive estimated breeding value (EBV’s) from uncorrected, additively (ACD), and multiplicatively corrected data (MCD) with percent range of superiority over herd average as 0.96–37.30, 1.49–38.77 and 0.99–38.53, respectively. These findings indicated that ACD and MCD discriminated among the sires to the maximum extent as compared to uncorrected data. The rank correlations among EBV’s of sires estimated from uncorrected, ACD and MCD were very high (0.98) revealing that both additive and multiplicative correction factors were equally effective in evaluating the sires. As far as comparison among both the age correction factors is concerned, multiplicative age correction factors were more effective in cow evaluation, whereas additive age correction factors seemed to be more effective for sire evaluation.